Análisis a los estados financieros de la empresa de servicios de telecomunicaciones - Celi Jaramillo, Erika Maricela (2023)
The present Curricular Integration Work called: Analysis of the financial statements of the telecommunications services company "Saraguros net" of the Saraguro canton, period 2020-2021, was developed with the purpose of evaluating the economic-financial position, through the application of the vertical and horizontal analysis of the financial statements of the company, knowing the levels of liquidity, indebtedness, activity, productivity and profitability through financial indicators, finally giving conclusions and recommendations in order to provide a contribution that allows the manager and executives correct decision making. For the development of the work, it was based on the application of different methods, starting from the scientific method where the elaboration of the theoretical framework was fulfilled based on the concepts, procedures and techniques in relation to financial analysis and application of indicators; Likewise, the deductive method that was applied in the review of the theoretical references, collecting bibliographic information from general topics to particular ones; the inductive method was used establishing the variations that occurred from one period to another, through the analysis and knowing the conditions of liquidity, solvency and profitability to give more detailed conclusions; the analytical and synthetic method that allowed analyzing and interpreting the financial statements provided by the company, which allowed knowing the economic-financial situation through the analysis and financial indicators and later making a report with all the results found; finally, the mathematical and statistical method that facilitated the interpretation of the different calculations and formulas that determined the percentages of the groups and subgroups of the analyses, in such a way that it allows obtaining reliable and real results. Next, the proposed objectives are fulfilled, for this it was necessary to evaluate the structure of the financial statements of the company "Saraguros net", which allowed the execution of the vertical and horizontal analysis of each study period, measuring the proportional weight and the variations that make up the economic-financial structure; Regarding the financial structure, the assets are represented by the current tax assets account with 45.75% in 2020 and 53.93% in 2021, originated by the tax credit in favor of the company (VAT) and by the income tax advance. Among the liabilities, the most representative are the accounts and documents payable with 185.43% and 181.16% for the periods 2020-2021 respectively, demonstrating that the company has a high level of debts and obligations payable to suppliers. Regarding its economic structure, expenses are the ones that have the greatest contribution, being 145.95% in 2020, mainly originated by the sales expenses account with 10 126.84% due to the fact that the company does not maintain adequate management of the expenses and is assuming part of the service provided in the maintenance of installation materials and internet service and is not being charged by customers, generating a loss for the year of $-188,216.71; while for the year 2021 the one that has the greatest contribution is the income with a total of $499,369.89, which is represented by the efficient profit of the provision of internet services and installation with 99.78%, despite this It must be taken into account that the company cancels a high value in sales expenses. In addition, the horizontal analysis was carried out, establishing the variations that each one of the accounts of the financial statements has suffered as an increase or decrease, determining a decrease in current tax assets of -4.35%, accounts and documents payable of - 20.72% and equity of -23.01%, in terms of income, they rise by 31.37% and expenses decrease by -15.16%, which allows the company to continue with the operation and daily activities of the company In relation to the financial indicators, the result is that the liquidity of the company is worrisome, resulting in $-105,611.65 in 2020 and $-80,983.79 in 2020, causing the default of outstanding obligations, the degree of indebtedness It is high in the two years, especially in 2020, reaching over 50%, that is to say that by 2020 there is a value of $2.13 and $2.08 in 2021, which shows that the company, by maintaining more debts is exposed to a greater risk of not meeting its obligations; Regarding total productivity, the company obtains profits through the provision of services in the year 2020, however, this is affected by the high level of expenses that originate. Finally, a financial analysis report is presented that contains the results obtained, which reflects the economic and financial situation of the telecommunications company "Saraguros Net" for the period 2020-2021, conclusions and recommendations that serve as a guide for administrative staff and partners, to improve performance and decision making.